Effects of zearalenone, α-zearalenol, and genistein on boar sperm motility in vitro - Adéla Krejcárková; Petra Folková; Ondřej Šimoník; Martina Šašková; Romana Krejčířová; Ondřej Drábek; Radko Rajmon (Czech Journal of Animal Science, 2017)
Genistein (GEN) and zearalenone (ZEA), environmental oestrogens commonly present in feedstuff for pigs, are known for their effects on reproductive functions. The aim was to verify the in vitro effects of 0.5-20 µM concentrations of GEN, ZEA and its metabolite α-zearalenol (α-ZOL) on pig sperm motility. A dose-dependent increase of the immotile sperm amount against fast and medium-fast sperm clusters was observed with all three oestrogens from the lowest concentrations tested. Individual CASA (computer-assisted sperm analysis) parameters of motile sperms seemed to be less sensitive indicators. This should be considered especially in toxicological research on a sperm model. Background of inconsistencies in to date-published papers is discussed. The results shift the effective concentrations of ZEA, α-ZOL, and GEN to values achievable in vivo and raises the questions of risk assessment of these compounds in pig reproduction.